Lead-free high Curie temperature piezoelectric ceramic material and preparation method thereof

By doping M' and Ta into CaBi2Nb2O9, a pseudo-tetragonal phase structure is constructed, which solves the problem of limited use ability of existing lead-based piezoelectric ceramics in high-temperature environments, and improves the piezoelectric properties and dielectric properties of piezoelectric ceramics, adapts to high-temperature environments, and reduces the threat to the environment and human health.

CN119504252APending Publication Date: 2025-02-25XIDIAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411656294.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing lead-based piezoelectric ceramics have limited ability to use in high-temperature and high-pressure environments, and lead materials pose a threat to the environment and human health. The piezoelectric performance of CaBi2Nb2O9 high-temperature piezoelectric ceramics is poor and difficult to be used in industrial production.

Method used

By doping M' and Ta into CaBi2Nb2O9, a pseudo-tetragonal phase structure is constructed, the degree of transformation between the orthogonal phase to the tetragonal phase is increased, and the piezoelectric constant and dielectric properties of the piezoelectric ceramic are improved.

Benefits of technology

It has achieved the improvement of the piezoelectric properties and dielectric properties of piezoelectric ceramics at high Curie temperatures, adapt to high temperature environments, and reduces the threat to the environment and human health.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119504252A_ABST
    Figure CN119504252A_ABST
Patent Text Reader

Abstract

The invention relates to a lead-free high Curie temperature piezoelectric ceramic material and a preparation method thereof, the chemical formula of the piezoelectric ceramic material is CaBi2Nb1.9 (M'xTa1-x) 0.1 O9, M'represents a first element, and x is more than 0 and less than or equal to 0.5; the ion radius of the first element is # imgabs0 # or # imgabs1 #. According to the invention, M'and Ta are doped into CBN, so that a pseudo-tetragonal phase structure is constructed, the transformation degree from an orthogonal phase to a tetragonal phase is increased, the piezoelectric constant of the piezoelectric ceramic material is improved while the piezoelectric ceramic material is ensured to have high Curie temperature, and in addition, the piezoelectric constant of the piezoelectric ceramic material is improved. Nb is partially replaced by M'and Ta, so that the distortion degree of an NbO6 hexahedron is increased, and the dielectric property and ferroelectric property of the piezoelectric ceramic material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of piezoelectric ceramic materials, and in particular relates to a lead-free high Curie temperature piezoelectric ceramic material and a preparation method thereof. Background Art

[0002] The widespread application of piezoelectric ceramics began with the discovery of their excellent piezoelectric properties, especially lead zirconate titanate PZT piezoelectric ceramics, which exhibit the best electrical properties near the quasi-modular phase boundary. However, with the advancement of science and technology, the demand for device performance in scientific research and application fields continues to increase, such as high Curie temperature, high power characteristics, high-frequency stability, a wide operating temperature range and adaptability. Therefore, researchers are seeking new functional materials with better performance to meet the needs of aerospace, detection, energy and other fields.

[0003] The Curie temperature of traditional lead-based piezoelectric ceramics often does not exceed 400°C, and the reliable use temperature is generally below 300°C, which limits its ability to be used for a long time in harsh environments such as high temperature and high pressure, which has become the focus of current research. In addition, considering the harm that lead-based piezoelectric ceramics may cause to human health and the ecological environment during production and disposal, the research on lead-free piezoelectric ceramics has attracted much attention based on sustainable development considerations.

[0004] CaBi2Nb2O9 (CBN) high temperature piezoelectric ceramics have many advantages such as high Curie temperature, low dielectric loss, high resistivity, low aging rate and high dielectric breakdown strength, and have attracted much attention in the field of high temperature and high frequency special needs. However, due to the high Curie temperature of CBN high temperature piezoelectric ceramics and the bismuth layered structure of CBN high temperature piezoelectric ceramics, CBN high temperature piezoelectric ceramics are affected by the large coercive field and limited ferroelectric spontaneous polarization, resulting in poor piezoelectric performance and difficulty in polarization in actual industrial production, which limits its application. Summary of the invention

[0005] In order to solve the above problems existing in the prior art, the present invention provides a lead-free high Curie temperature piezoelectric ceramic material and a preparation method thereof. The technical problem to be solved by the present invention is achieved by the following technical solutions:

[0006] The first aspect of the present invention provides a lead-free high Curie temperature piezoelectric ceramic material, the chemical formula of which is CaBi2Nb 1.9 (M' x Ta 1-x ) 0.1 O9, where M' represents the first element, 0<x≤0.5;

[0007] The ionic radius of the first element is Alternatively, the ionic radius of the first element is

[0008]

[0009] In one achievable manner, the ionic radius of the first element is When the first element comprises: Sb, W, Al or Ti;

[0010] The ionic radius of the first element is When the first element includes: Li, Mg, Zn, Zr or Hf.

[0011] In one implementable manner, the first element is Sb; 0.125≤x≤0.2.

[0012] The second aspect of the present invention provides a method for preparing a lead-free high Curie temperature piezoelectric ceramic material, which is used to prepare the lead-free high Curie temperature piezoelectric ceramic material provided by the first aspect of the present invention, comprising the following steps:

[0013] S1: According to the chemical formula CaBi2Nb 1.9 (M' x Ta 1-x ) 0.1 The ratio of Ca, Bi, Nb, M' and Ta in O9 is: Ca-containing compound, Bi-containing compound, Nb-containing compound, M'-containing compound and Ta-containing compound are weighed to obtain a mixed powder; wherein M' represents the first element, 0<x≤0.5; the ion radius of the first element is Alternatively, the ionic radius of the first element is

[0014] S2: ball milling, drying, grinding, sieving and pre-calcining the mixed powder in sequence to obtain a primary pre-calcined powder;

[0015] S3: ball milling, drying, grinding, sieving and pre-calcining the primary pre-calcined powder in sequence to obtain a secondary pre-calcined powder;

[0016] S4: ball milling and drying the secondary pre-burned powder in sequence to obtain a prefabricated mixed dry powder;

[0017] S5: adding a binder to the prefabricated mixed dry powder to granulate, sieve, and then press to obtain a ceramic green body;

[0018] S6: performing densification treatment on the ceramic green body to obtain a dense green body;

[0019] S7: sequentially performing binder removal, powder embedding and sintering on the dense green body to obtain a ceramic green body;

[0020] S8: Thinning, polishing, cleaning and drying the ceramic blank in sequence to obtain CaBi2Nb1.9 (M' x Ta 1-x ) 0.1 O9 piezoelectric ceramics.

[0021] In one achievable manner, the ionic radius of the first element is When the M'-containing compound includes: a Sb-containing compound, a W-containing compound, an Al-containing compound or a Ti-containing compound;

[0022] The ionic radius of the first element is When the M'-containing compound comprises: a Li-containing compound, a Mg-containing compound, a Zn-containing compound, a Zr-containing compound or a Hf-containing compound.

[0023] In one achievable manner, the M′-containing compound is a Sb-containing compound, and 0.125≤x≤0.2.

[0024] In one achievable manner, in step S2, step S3 and step S4, ball milling includes:

[0025] Ball milling is performed using anhydrous ethanol as a grinding agent, dioctyl phthalate as a dispersant, and zirconium oxide balls as ball milling media, wherein the ratio of the powder to be ball milled to anhydrous ethanol is 1g:1.5-2.0ml, the mass ratio of the zirconium oxide balls to the powder to be ball milled is 2-2.5:1, the ball milling time is 12-24h, and the ball milling speed is 350r / min.

[0026] In one achievable manner, in step S2, step S3 and step S4, the drying time is 3 to 4 hours, and the drying temperature is controlled to be 60 to 80°C.

[0027] In one achievable manner, in step S2 and step S3, pre-burning includes:

[0028] Put the powder to be pre-fired into a crucible and cover it, heat it to 600°C at a rate of 4°C / min, keep it warm for 100 minutes, then heat it to 900°C at a rate of 2°C / min, and keep it warm for 2 to 3 hours.

[0029] In one achievable manner, step S7 includes:

[0030] S701: heating the dense green body to 120° C. at a rate of 2-3° C. / min under air atmosphere, keeping the temperature for 10 min, and then slowly heating the green body to 600-650° C. at a rate of 1.5-2.5° C. / min, keeping the temperature for 2-4 h, to obtain a dense green body after debinding;

[0031] S702: sintering the prefabricated mixed dry powder at 1200° C. for 2 to 3 hours to obtain cooked powder, and embedding the dense green body after debinding with the cooked powder to obtain a dense green body after embedding;

[0032] S703: heating the dense green body after embedding powder to 850-950°C at a rate of 4°C / min in air atmosphere, keeping the temperature for 100 minutes, and then heating it to 1150-1250°C at a rate of 2°C / min, and firing at a constant temperature for 2-3 hours to obtain the ceramic green body.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] The lead-free high Curie temperature piezoelectric ceramic material of the present invention constructs a pseudo-tetragonal phase structure by doping M' and Ta into CBN, thereby increasing the degree of transformation from the orthorhombic phase to the tetragonal phase, and improving the piezoelectric constant of the piezoelectric ceramic material while ensuring that the piezoelectric ceramic material has a high Curie temperature. In addition, since M' and Ta partially replace Nb, the degree of distortion of the NbO6 hexahedron is increased, thereby improving the dielectric properties and ferroelectric properties of the piezoelectric ceramic material. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 It is a flowchart of the steps of a method for preparing a lead-free high Curie temperature piezoelectric ceramic material provided by an embodiment of the present invention;

[0036] Figure 2 The CaBi2Nb provided in the embodiment of the present invention 1.9 (Sb x Ta 1-x ) 0.1 Piezoelectric constant diagram of O9 piezoelectric ceramic material;

[0037] Figure 3 The CaBi2Nb provided in the embodiment of the present invention 1.9 (Sb x Ta 1-x ) 0.1 PE curve of O9 piezoelectric ceramic material;

[0038] Figure 4 The CaBi2Nb provided in the embodiment of the present invention 1.9 (Sb x Ta 1-x ) 0.1 Remanent polarization intensity diagram of O9 piezoelectric ceramic material;

[0039] Figure 5 The CaBi2Nb provided in the embodiment of the present invention 1.9 (Sb x Ta 1-x )0.1 The dielectric constant of O9 piezoelectric ceramic material varies with temperature;

[0040] Figure 6 The CaBi2Nb provided in the embodiment of the present invention 1.9 (Sb x Ta 1-x ) 0.1 The dielectric loss of O9 piezoelectric ceramic material varies with temperature;

[0041] Figure 7 The CaBi2Nb provided in the embodiment of the present invention 1.9 (Mg 0.08 Ta 0.92 ) 0.1 The dielectric constant of O9 piezoelectric ceramic material varies with temperature;

[0042] Figure 8 The CaBi2Nb provided in the embodiment of the present invention 1.9 (Mg 0.08 Ta 0.92 ) 0.1 The dielectric loss of O9 piezoelectric ceramic material varies with temperature. DETAILED DESCRIPTION

[0043] The present invention is further described in detail below with reference to specific embodiments, but the embodiments of the present invention are not limited thereto.

[0044] Embodiment 1

[0045] This embodiment provides a lead-free high Curie temperature piezoelectric ceramic material. The chemical formula of the piezoelectric ceramic material is CaBi2Nb 1.9 (M' x Ta 1-x ) 0.1 O9, where M' represents the first element, 0<x≤0.5. The ionic radius of the first element is Alternatively, the ionic radius of the first element is

[0046] Specifically, the radii of Nb and Ta In this embodiment, M' and Ta are doped into CBN, and M' and Ta enter the B position of the bismuth layer to replace the B position element. In this embodiment, the B position element is Nb, that is, M' and Ta partially replace Nb. Since the ionic radius of the first element and Nb is different, the partial replacement of Nb by M' and Ta can transform the crystal structure from the orthorhombic phase to the tetragonal phase, thereby improving the piezoelectric properties of the piezoelectric ceramic material. In addition, after doping with M' and Ta, the degree of distortion of the NbO6 hexahedron is increased, and the resistivity of the piezoelectric ceramic material is increased. The doped piezoelectric ceramic material can apply a larger polarization voltage to completely flip the ferroelectric domain, thereby improving its ferroelectric properties and dielectric properties.

[0047] In this embodiment, the ionic radius of the first element is When the first element includes: Sb, W, Al or Ti. The ionic radius of the first element is When the first element includes: Li, Mg, Zn, Zr or Hf.

[0048] In one achievable manner, M' is Sb, 0.125≤x≤0.2.

[0049] Specifically, the preparation method of the lead-free high Curie temperature piezoelectric ceramic material of this embodiment is described, see Figure 1 , Figure 1 The present invention provides a step flow chart of a method for preparing a lead-free high Curie temperature piezoelectric ceramic material.

[0050] This embodiment provides a method for preparing a lead-free high Curie temperature piezoelectric ceramic material, comprising:

[0051] S1: According to the chemical formula CaBi2Nb 1.9 (M' x Ta 1-x ) 0.1 The ratio of Ca, Bi, Nb, M' and Ta in O9 is: Weigh the compound containing Ca, the compound containing Bi, the compound containing Nb, the compound containing M' and the compound containing Ta to obtain a mixed powder; wherein M' represents the first element, 0<x≤0.5; the ionic radius of the first element is Alternatively, the ionic radius of the first element is

[0052] In this embodiment, when the ionic radius of the first element is When the ion radius of the first element is When the M'-containing compound includes: a Li-containing compound, a Mg-containing compound, a Zn-containing compound, a Zr-containing compound or a Hf-containing compound. Exemplarily, the Ca-containing compound is CaCO3 powder, the Bi-containing compound is Bi2O3 powder, the Nb-containing compound is Nb2O5 powder, the M'-containing compound is M' oxide powder, and the Ta-containing compound is Ta2O5 powder.

[0053] S2: The mixed powder is ball-milled, dried, ground, sieved and pre-burned in sequence to obtain a primary pre-burned powder.

[0054] S3: The primary pre-burned powder is subjected to ball milling, drying, grinding, sieving and pre-burning in sequence to obtain a secondary pre-burned powder.

[0055] In step S2 and step S3, pre-burning includes:

[0056] Put the powder to be pre-fired into a crucible and cover it, heat it to 600°C at a rate of 4°C / min, keep it warm for 100 minutes, then heat it to 900°C at a rate of 2°C / min, and keep it warm for 2 to 3 hours.

[0057] Specifically, the powder to be pre-fired is poured into the pre-fired crucible and compacted and covered to form a closed space in the pre-fired crucible, and pre-fired in the atmosphere. It should be understood that the powder to be pre-fired in step S2 is a mixed powder, and the powder to be pre-fired in step S3 is a primary pre-fired powder.

[0058] In this embodiment, the grinding and screening in step S2 and step S3 include: grinding the dried powder into powder in a corundum mortar, and screening with a 60-mesh screen.

[0059] S4: ball milling and drying the secondary pre-burned powder in sequence to obtain a prefabricated mixed dry powder.

[0060] In step S2, step S3 and step S4, ball milling includes:

[0061] The ball milling is performed using anhydrous ethanol as a grinding agent, dioctyl phthalate as a dispersant, and zirconium oxide balls as a ball milling medium, wherein the ratio of the powder to be ball milled to anhydrous ethanol is 1g:1.5-2.0ml, the mass ratio of the zirconium oxide balls to the powder to be ball milled is 2-2.5:1, the ball milling time is 12-24h, and the ball milling speed is 350r / min. It should be understood that the ball milling liquid is obtained after ball milling.

[0062] In step S2, step S3 and step S4, the drying time is 3 to 4 hours, and the drying temperature is controlled at 60 to 80°C.

[0063] Specifically, the ball milling liquid obtained after ball milling is placed in a glass dish for drying, and the surface of the glass dish is wrapped with a plastic wrap with small ventilation holes left on the plastic wrap to prevent a large amount of volatilization of Bi2O3.

[0064] Furthermore, in step S4, ball milling and drying are repeated three times.

[0065] S5: adding a binder to the prefabricated mixed dry powder to granulate, sieve, and then press to obtain a ceramic green body.

[0066] Specifically, step S5 includes:

[0067] S501: Weigh a binder and dissolve it in water to obtain a binder solution with a mass percentage concentration of 7% to 8%. In this embodiment, the binder is polyvinyl alcohol (PVA).

[0068] S502: Add the binder solution to the pre-made mixed dry powder, and perform granulation in a corundum mortar to obtain powder particles.

[0069] S503: Pass the powder through a 60-mesh sieve.

[0070] S504: The powder particles obtained after screening are pressed into shape at a pressure of 4 MPa to obtain a ceramic green body.

[0071] S6: Densification treatment is performed on the ceramic green body to obtain a dense green body.

[0072] Specifically, the ceramic green body is placed in a packaging bag and vacuumed. After the vacuuming is completed, it is placed in an isostatic pressing device and densified at a pressure of 30 MPa for 15 minutes.

[0073] S7: Debinding and sintering the dense green body in sequence to obtain a ceramic green body.

[0074] Specifically, step S7 includes:

[0075] S701: The dense green body is heated to 120°C at a rate of 2-3°C / min in an atmospheric atmosphere, kept at this temperature for 10 minutes, and then slowly heated to 600-650°C at a rate of 1.5-2.5°C / min, kept at this temperature for 2-4 hours, to remove the moisture carried in the dense green body during granulation, and obtain a dense green body after debinding.

[0076] S702: sintering the prefabricated mixed dry powder at 1200° C. for 2 to 3 hours to obtain cooked powder, and embedding the dense green body after debinding with the cooked powder to obtain a dense green body after embedding.

[0077] S703: The dense green body after embedding powder is heated to 850-950°C at a rate of 4°C / min in air atmosphere, kept at this temperature for 100 minutes, and then heated to 1150-1250°C at a rate of 2°C / min, and fired at this temperature for 2-3 hours to obtain a ceramic green body. In this embodiment, the sintering device is a muffle furnace.

[0078] S8: Thinning, polishing, cleaning and drying the ceramic blank in sequence to obtain CaBi2Nb 1.9 (M' x Ta 1-x ) 0.1 O9 piezoelectric ceramics.

[0079] Specifically, step S8 includes:

[0080] S801: The ceramic blank is thinned to 0.35-0.45 mm on both the upper and lower surfaces using 200-mesh, 800-mesh and 1200-mesh sandpapers in a grinding machine.

[0081] S802: placing the ceramic blank after the thinning process on a polishing machine and performing polishing process using a suspension.

[0082] S803: The polished ceramic blank is suspended in a test tube, anhydrous ethanol is added, ultrasonicated in an ultrasonic cleaner for 100 to 120 minutes, and then dried on a heating table at a drying temperature of 120°C. After drying, CaBi2Nb 1.9 (M' x Ta 1-x ) 0.1 O9 piezoelectric ceramics.

[0083] The present embodiment provides a lead-free high Curie temperature piezoelectric ceramic material. By doping M' and Ta into CBN, the degree of transformation from the orthorhombic phase to the tetragonal phase is increased, and the piezoelectric constant of the piezoelectric ceramic material is improved while ensuring that the piezoelectric ceramic material has a high Curie temperature. In addition, since M' and Ta partially replace Nb, the degree of distortion of the NbO6 hexahedron is increased, and the dielectric properties and ferroelectric properties of the piezoelectric ceramic material are improved. The raw materials used in the preparation process of the piezoelectric ceramic material are all common compounds, do not contain harmful elements such as lead, are environmentally friendly, and comply with the concept of green development. The lead-free high Curie temperature piezoelectric ceramic material provided in the present embodiment can adapt to high temperature environments and maintain good piezoelectric properties in high temperature environments, and can be widely used in aerospace and automotive industries.

[0084] Embodiment 2

[0085] Based on the first embodiment, this embodiment provides a lead-free high Curie temperature piezoelectric ceramic material, the chemical formula of which is CaBi2Nb 1.9 (Sbx Ta 1-x ) 0.1 O9, and changing the value of x to 0.125, 0.15, 0.175 and 0.20, we get CaBi2Nb 1.9 (Sb 0.125 Ta 0.875 ) 0.1 O9, CaBi2Nb 1.9 (Sb 0.15 Ta 0.85 ) 0.1 O9, CaBi2Nb 1.9 (Sb 0.175 Ta 0.825 ) 0.1 O9 and CaBi2Nb 1.9 (Sb 0.2 Ta 0.8 ) 0.1 O9 four kinds of piezoelectric ceramic materials, and the performance tests are carried out on the piezoelectric ceramic materials after electrode plating, so as to further illustrate the lead-free high Curie temperature piezoelectric ceramic material provided in this embodiment.

[0086] In this embodiment, CaBi2Nb 1.9 (Sb x Ta 1-x ) 0.1 O9 is thinned to 0.4 mm. Specifically, during the piezoelectric constant d33 test, the material thickness is proportional to the applied voltage. CaBi2Nb 1.9 (Sb x Ta 1-x ) 0.1 When the thickness of O9 is 0.4 mm, the ceramic sample is not easily broken down, and the corresponding polarization voltage can make the d33 test value reach the highest test range.

[0087] In this embodiment, the electrode plating includes:

[0088] Silver electrodes with a diameter of 1 mm and 0.8 mm were screen-printed on the upper and lower surfaces of the piezoelectric ceramic respectively, and then dried on a heating table with a temperature of 150°C for 30 minutes. After drying, the piezoelectric ceramic was placed in a muffle furnace for silver sintering treatment with a sintering temperature of 600-650°C and a holding time of 120 minutes.

[0089] Place the electrode-plated piezoelectric ceramic in 180°C silicone oil and apply 2-5kV / mm electric field polarization for 15-20 minutes. After the polarization, take it out and cool it to room temperature. Use a quasi-static d33 tester to measure its d33 value. 1.9 (Sb x Ta 1-x )0.1 The test results of d33 value of O9 piezoelectric ceramic material are as follows Figure 2 As shown, pure CBN piezoelectric ceramics are undoped CBN piezoelectric ceramic materials in the prior art. The d33 of pure CBN piezoelectric ceramics is 6pC / N. The CaBi2Nb 1.9 (Sb x Ta 1-x ) 0.1 The d33 of O9 piezoelectric ceramic material is 11-13pC / N, and when x is less than 0.175, as x increases, that is, CaBi2Nb 1.9 (Sb x Ta 1-x ) 0.1 As the Sb content in O9 increases, d33 continues to increase. When X=0.175, d33 is as high as 13pC / N.

[0090] CaBi2Nb 1.9 (Sb x Ta 1-x ) 0.1 The ferroelectric properties test results of O9 piezoelectric ceramic materials are as follows Figure 3 and Figure 4 As shown, when x = 0, it is CaBi2Nb 1.9 Ta 0.1 O9, wherein Ta element replaces Nb. Figure 3 The horizontal axis is the electric field strength (Electric Field, E), and the vertical axis is the polarization strength (Polarization, P). Figure 3 It can be seen that the PE curve of the piezoelectric ceramic material after Sb and Ta substitution is more saturated than that of pure CBN piezoelectric ceramics. Figure 3 It can be seen that the Ta element replaces Nb and increases the residual polarization strength Pr of the piezoelectric ceramic material from 0.83μc / cm 2 Increased to 2.02μc / cm 2 With the addition of Sb, the Pr of the piezoelectric ceramic material is further increased, and finally reaches the highest value of 6.34μc / cm when x=0.175. 2 , and then began to decline. This shows that Sb and Ta increase the degree of distortion of NbO6 and improve the residual polarization strength of piezoelectric ceramic materials. The higher the residual polarization strength, the better the ferroelectric properties of the material. When the Sb content is too high (x = 0.2), the Sb element accumulates at the grain boundary, hindering the movement of the ferroelectric domain wall, thereby reducing its ferroelectric properties.

[0091] The CaBi2Nb obtained when x is 0.15 and 0.175 was measured by high temperature dielectric instrument. 1.9 (Sb 0.15Ta 0.85 ) 0.1 O9 and CaBi2Nb 1.9 (Sb 0.175 Ta 0.825 ) 0.1 Dielectric constant ε of O9 r The dielectric loss tanδ is tested and the Curie temperature is obtained. The test results are as follows Figure 5 and Figure 6 As shown, from Figure 5 It can be seen that the CaBi2Nb 1.9 (Sb x Ta 1-x ) 0.1 O9 Piezoelectric ceramic material Curie temperature T c There is no significant difference between pure CBN piezoelectric ceramics and the CaBi2Nb 1.9 (Sb x Ta 1-x ) 0.1 The dielectric constant of O9 piezoelectric ceramic material is higher than that of pure CBN piezoelectric ceramic. Figure 4 It can be seen that the CaBi2Nb 1.9 (Sb x Ta 1-x ) 0.1 O9 piezoelectric ceramics significantly reduce the dielectric loss tanδ in the high temperature part (600-750℃).

[0092] Embodiment 3

[0093] Based on the first embodiment, this embodiment provides a lead-free high Curie temperature piezoelectric ceramic material, the chemical formula of which is CaBi2Nb 1.9 (Mg 0.08 Ta 0.92 ) 0.1 O9. The CaBi2Nb 1.9 (Mg 0.08 Ta 0.92 ) 0.1 The performance test was performed after the O9 piezoelectric ceramic material was plated with electrodes to further illustrate the lead-free high Curie temperature piezoelectric ceramic material provided in this embodiment.

[0094] In this embodiment, the electrode plating includes:

[0095] The upper and lower surfaces of the piezoelectric ceramic are screen-printed with platinum electrodes with a diameter of 1 mm and 0.8 mm respectively, and then dried on a heating table with a temperature of 150°C for 30 minutes. After drying, the piezoelectric ceramic is placed in a muffle furnace for platinum sintering. The sintering temperature of the platinum electrode is 1000-1100°C and the insulation time is 10-30 minutes.

[0096] The dielectric constant ε of the piezoelectric ceramics with platinum electrodes was measured using a high-temperature dielectric instrument. r The dielectric loss tanδ is tested and the Curie temperature is obtained. The test results are as follows Figure 3 and Figure 4 As shown. Figure 3 It can be seen that the CaBi2Nb 1.9 (Mg 0.08 Ta 0.92 ) 0.1 Curie temperature T of O9 piezoelectric ceramics c is 951°C, the CaBi2Nb 1.9 (Mg 0.08 Ta 0.92 ) 0.1 O9 piezoelectric ceramics have a high dielectric constant. Figure 4 It can be seen that the CaBi2Nb 1.9 (Mg 0.08 Ta 0.92 ) 0.1 O9 piezoelectric ceramics significantly reduce the dielectric loss tanδ in the high temperature part (600-800℃).

[0097] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the protection scope of the present invention.

Claims

1. A lead-free high Curie temperature piezoelectric ceramic material, characterized in that: The chemical formula of the piezoelectric ceramic material is CaBi2Nb 1.9 (M' x Ta 1-x ) 0.1 O9, where M' represents the first element, 0<x≤0.5; The ionic radius of the first element is Alternatively, the ionic radius of the first element is 2. The lead-free high Curie temperature piezoelectric ceramic material according to claim 1, characterized in that: The ionic radius of the first element is When the first element comprises: Sb, W, Al or Ti; The ionic radius of the first element is When the first element includes: Li, Mg, Zn, Zr or Hf.

3. The lead-free high Curie temperature piezoelectric ceramic material according to claim 2, characterized in that: The first element is Sb; 0.125≤x≤0.

2.

4. A method for preparing a lead-free high Curie temperature piezoelectric ceramic material, characterized in that: The method for preparing the lead-free high Curie temperature piezoelectric ceramic material according to any one of claims 1 to 3 comprises the following steps: S1: According to the chemical formula CaBi2Nb 1.9 (M' x Ta 1-x ) 0.1 The ratio of Ca, Bi, Nb, M' and Ta in O9 is: Ca-containing compound, Bi-containing compound, Nb-containing compound, M'-containing compound and Ta-containing compound are weighed to obtain a mixed powder; wherein M' represents the first element, 0<x≤0.5; the ion radius of the first element is Alternatively, the ionic radius of the first element is S2: ball milling, drying, grinding, sieving and pre-calcining the mixed powder in sequence to obtain a primary pre-calcined powder; S3: ball milling, drying, grinding, sieving and pre-calcining the primary pre-calcined powder in sequence to obtain a secondary pre-calcined powder; S4: ball milling and drying the secondary pre-burned powder in sequence to obtain a prefabricated mixed dry powder; S5: adding a binder to the prefabricated mixed dry powder to granulate, sieve, and then press to obtain a ceramic green body; S6: performing densification treatment on the ceramic green body to obtain a dense green body; S7: sequentially performing binder removal, powder embedding and sintering on the dense green body to obtain a ceramic green body; S8: Thinning, polishing, cleaning and drying the ceramic blank in sequence to obtain CaBi2Nb 1.9 (M' x Ta 1-x ) 0.1 O9 piezoelectric ceramics.

5. The method for preparing a lead-free high Curie temperature piezoelectric ceramic material according to claim 4, characterized in that: The ionic radius of the first element is When the M'-containing compound includes: a Sb-containing compound, a W-containing compound, an Al-containing compound or a Ti-containing compound; The ionic radius of the first element is When the M'-containing compound comprises: a Li-containing compound, a Mg-containing compound, a Zn-containing compound, a Zr-containing compound or a Hf-containing compound.

6. The method for preparing a lead-free high Curie temperature piezoelectric ceramic material according to claim 4, characterized in that: The M'-containing compound is a Sb-containing compound, and 0.125≤x≤0.

2.

7. The method for preparing a lead-free high Curie temperature piezoelectric ceramic material according to claim 4, characterized in that: In the step S2, the step S3 and the step S4, the ball milling includes: Ball milling is performed using anhydrous ethanol as a grinding agent, dioctyl phthalate as a dispersant, and zirconium oxide balls as ball milling media, wherein the ratio of the powder to be ball milled to anhydrous ethanol is 1g:1.5-2.0ml, the mass ratio of the zirconium oxide balls to the powder to be ball milled is 2-2.5:1, the ball milling time is 12-24h, and the ball milling speed is 350r / min.

8. The method for preparing a lead-free high Curie temperature piezoelectric ceramic material according to claim 4, characterized in that: In the step S2, the step S3 and the step S4, the drying time is 3 to 4 hours, and the drying temperature is controlled to be 60 to 80°C.

9. The method for preparing a lead-free high Curie temperature piezoelectric ceramic material according to claim 4, characterized in that: In the step S2 and the step S3, pre-burning includes: Put the powder to be pre-fired into a crucible and cover it, heat it to 600°C at a rate of 4°C / min, keep it warm for 100 minutes, then heat it to 900°C at a rate of 2°C / min, and keep it warm for 2 to 3 hours.

10. The method for preparing a lead-free high Curie temperature piezoelectric ceramic material according to claim 4, characterized in that: The step S7 comprises: S701: heating the dense green body to 120° C. at a rate of 2-3° C. / min under air atmosphere, keeping the temperature for 10 min, and then slowly heating the green body to 600-650° C. at a rate of 1.5-2.5° C. / min, keeping the temperature for 2-4 h, to obtain a dense green body after debinding; S702: sintering the prefabricated mixed dry powder at 1200° C. for 2 to 3 hours to obtain cooked powder, and embedding the dense green body after debinding with the cooked powder to obtain a dense green body after embedding; S703: heating the dense green body after embedding powder to 850-950°C at a rate of 4°C / min in air atmosphere, keeping the temperature for 100 minutes, and then heating it to 1150-1250°C at a rate of 2°C / min, and firing at a constant temperature for 2-3 hours to obtain the ceramic green body.